2010
DOI: 10.1016/j.atherosclerosis.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma soluble E-selectin and adiponectin with carotid plaque in patients with systemic lupus erythematosus

Abstract: Background Systemic lupus erythematosus (SLE) is associated with premature atherosclerosis but the mechanisms underlying this association are not understood. The role of endothelial dysfunction is hypothesized. Methods In predominantly non-Caucasian patients with SLE (n=119) and controls (n=71), carotid ultrasonography was performed and circulating endothelial cells (CECs), soluble endothelial protein C receptor and gene polymorphism at A6936G, soluble E-selectin (sE-selectin), and adiponectin were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 40 publications
7
55
6
Order By: Relevance
“…Insulin resistance per se as defined by the WHO criteria was more prevalent in lupus patients compared to controls (44.1% versus 24.8%) (Chung, Avalos et al 2007). Similarly to RA, increased levels of adiponectin have been reported in SLE patients (Sada, Yamasaki et al 2006;Chung, Long et al 2009;Vadacca, Margiotta et al 2009) and found to be associated with carotid plaque formation, as a physiologic attempt to limit endothelial damage (Sada, Yamasaki et al 2006;Vadacca, Margiotta et al 2009;Clancy and Ginzler 2010;Reynolds, Buyon et al 2010). Opposite are the findings reported by Chung et al, where lower levels of adiponectin were associated with insulin resistance, BMI and CRP but not with coronary atherosclerosis (Chung, Long et al 2009).…”
Section: Slecontrasting
confidence: 46%
“…Insulin resistance per se as defined by the WHO criteria was more prevalent in lupus patients compared to controls (44.1% versus 24.8%) (Chung, Avalos et al 2007). Similarly to RA, increased levels of adiponectin have been reported in SLE patients (Sada, Yamasaki et al 2006;Chung, Long et al 2009;Vadacca, Margiotta et al 2009) and found to be associated with carotid plaque formation, as a physiologic attempt to limit endothelial damage (Sada, Yamasaki et al 2006;Vadacca, Margiotta et al 2009;Clancy and Ginzler 2010;Reynolds, Buyon et al 2010). Opposite are the findings reported by Chung et al, where lower levels of adiponectin were associated with insulin resistance, BMI and CRP but not with coronary atherosclerosis (Chung, Long et al 2009).…”
Section: Slecontrasting
confidence: 46%
“…In contrast, other authors did not find any difference in adiponectin levels between SLE patients and controls (53,54). Interestingly, adiponectin levels are increased in SLE patients with carotid plaques (106) and in renal SLE-associated vasculopathy (107).…”
Section: Adiponectin and Rheumatic Diseasesmentioning
confidence: 82%
“…Adiponectin were significantly higher in the SLE patients with plaque compared to those without plaque in multivariate analysis, indicating that adiponectin may serve as independent predictor of carotid plaque [15]. Adiponectin was negatively associated with BMI, insulin resistance (IR) and C-reactive protein (ρ=−0.40, p<0.001; ρ= −0.38, p<0.001; ρ=−0.22, p=0.02, respectively) [17,18], and ghrelin levels correlate with homocysteine [18].…”
Section: Systematic Review Of Relationship Between Adipokine Levels Amentioning
confidence: 96%
“…Sixteen studies were selected for full-text review based on the title and abstract, but five of these were excluded because they were a review or had no data on the adipokine levels. Finally, 11 articles met the inclusion criteria for this meta-analysis ( Figure 1) [12][13][14][15][16][17][18][19][20][21][22]. Three of the eligible studies included data on two different groups [13,18,20] that were treated independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation